Globalization and labor market outcomes: wage bargaining, search frictions, and firm heterogeneity - Gabriel J. Felbermayr; Julien Prat; Hans-Jörg Schmerer (Institute for the Study of Labor (IZA), 2008)
We introduce search unemployment à la Pissarides into Melitz' (2003) model of trade with heterogeneous firms. We allow wages to be individually or collectively bargained and analytically solve for the equilibrium. We find that the selection effect of trade influences labor market outcomes. Trade liberalization lowers unemployment and raises real wages as long as it improves aggregate productivity net of transport costs. We show that this condition is likely to be met by a reduction in variable trade costs or the entry of new trading countries. On the other hand, the gains from a reduction in fixed market access costs are more elusive. Calibrating the model shows that the positive impact of trade openness on employment is significant when wages are bargained at the individual level but much smaller when wages are bargained at the collective level.
Keywords: F12; 330; Trade liberalization; unemployment; search model; firm heterogeneity; Außenhandelsliberalisierung; Beschäftigungseffekt; Intraindustrieller Handel; Arbeitsuche; Arbeitslosigkeit; Lohnverhandlungstheorie; Globalisierung; Reallohn; Theorie